The effects of personal green spaces on human’s mental health and anxiety symptoms during COVID-19: The case of apartment residents in Tehran - Khaledi, Hanieh Jafari; Faizi, Mohsen; Khakzand, Mehdi (Frontiers in Built Environment, 2022)
The governments implemented social distancing and isolation with the spread of Covid-19. However these ways efficiently prevent coronavirus transmission, but they caused unprecedented changes in most people’s day-to-day lives. One of the concerns is mental health, that many experts are concerned about the tsunami of mental illness during and after Coronavirus. Be exposed to nature has an efficient role in mental health. Under pandemic conditions, people reduced their outdoor activities, but personal green spaces are still available. This research assessed the impacts of these spaces as an alternative to public greenspace and its benefits during Covid-19 on mental health and generalized anxiety disorder. Accordingly, by designing an online self-administered questionnaire, 700 residents of Tehran apartments were evaluated. A structural equation model was created. The results demonstrate that using personal green space has a negative correlation and significant impact on general mental health and generalized anxiety disorder. It also plays a more substantial role in reducing depression than its role in reducing anxiety among individuals. Therefore, maximum land use policies should be reviewed. Also, green spaces should be given more attention in post-covid designs on a macro scale to a small scale.